Isolated gastrointestinal histoplasmosis: A rare diagnosis of pediatric chronic abdominal pain - Acharyya, Bhaswati C.; Acharyya, Saumyabrata; Chakrabarty, Hema (Indian journal of pathology & microbiology, 2021)
Gastrointestinal (GI) histoplasmosis usually occurs as a part of disseminated histoplasmosis in immunocompromised or elderly subjects. Isolated histoplasmosis involving the GI tract in an immunocompetent host is very rare. It is also not considered as an etiology for chronic abdominal pain in children. Here we present an 8-year-old boy with abdominal pain and weight loss who underwent treatment for tuberculosis but on reinvestigation was diagnosed as GI histoplasmosis. He responded well to treatment and achieved good catch up growth.